Spatio-temporal analysis of rainfall data in Kuala Krai Kelantan. Issue 1 (August 2021) - Muhammad, M; Ibrahim, Q A Q; Ghani, M S M; Jemali, N; Awang, N R
Abstract: This paper interpreted spatio-temporally the relationship between event of weather activities and flooding in Kuala Krai Kelantan. During the Kelantan big yellow flood event in December 2014, Kuala Krai was one of the worst affected area with the rarity of the return period approximately 1 in 1000 years. Many say this is due to the unusual occurrence of extreme rainfall. Therefore, this research work on spatio-temporal analysis of the time series rainfall data in Kuala Krai Kelantan, to describe and determine the behaviour and pattern of the data. The data on the monthly amount of rainfall between (2013-2019), were collected from Department Irrigation and Drainage (DID). The main aim of this study is to statistically determine whether it is true the flooding in Kuala Krai Kelantan on 2014 is because of heavy rainfall. The collected rainfall data had been spatially analysed using ArcGIS to compare the distribution of rainfall from year 2013 to 2019. Then, the trend pattern of the data had been determined using Mann Kendall Test and Sen's slope Test. From those analysis it can be concluded that the huge amount of rainfall intensity is the major factor that contribute the extreme flood event in Kuala Krai Kelantan on December 2014.